CARA DETEKSI YODIUM SEMI-KUANTITATIF SEDERHANA PADA GARAM RUMAH TANGGA: UJI KELAYAKAN DI LAPANGAN - Purawisastra, Suryana; Saidin, Sukati; Kartono, Djoko; Widagdo, Dhuto (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2012)
A Simple Field Kit-Test For Semi-Quantitative Iodine Content In The Iodated Salt of Households: An Appropriate-Test In The Field. Background: A programme of iodized salt for human consumption has been in operation in Indonesia for over 3 decades. Effectiveness of the programmed is to control and regular monitoring of edible salt for iodine. Therefore, it is required a simple field kit for semi quantitative estimation of iodine content in the iodated salt in the households. Methods: Thetest was performed by forty-five of house wives and forty-five of "kader". The samples of salt respectively were provided from their houses. The test was carried out by dropping of 2-3 drops of test-kit solution to surface of the salt. Observe the color appears on the surface of salt, and then compare to the color of photo of standard. The yellow color (code 1) was equalto 0 part per million of iodine (0 ppm), the color of yellow greenish (code 2) was equal to the iodine content of upper zero up to 15 ppm (>0 ppm - <15 ppm), the color of green yellowish (code 3) was equal to the iodine content between upper 15 to the below of 30 ppm (>15 ppm- < 30 ppm), and the color of green bluish (code 4) was equal to 30 ppm and above (> 30ppm). As comparison, the samples of salt were also analyzed quantitatively for the iodine content in laboratory using the standard method. Results: The result of iodine analysis in sample of salt done by using the standard method in the laboratory showed that the iodine content was varied. The estimate precision of iodine content in the salt by the house wives were 63,6% for the iodine content > 0 ppm-< 15 ppm; 87.5% for the iodine content > 15 ppm- < 30 ppm; 61.1% for the iodine content >30 ppm. While"kader" were 37,5% for the iodine content > 0 ppm - <15 ppm; 86.7% for the iodine content > 15 ppm - < 30 ppm; 72.7% for the iodine content > 30 ppm. Its Predictive Positive Value (PPV) in the iodine content 15 ppm > -< 30 ppm was 88% for the house wives and 87% for "kader". Its sensitivity was above 45% and its true prevalence (Se + Sp) was above 100% for all iodine concentration, except for zero ppm. Conclusions: The highest precisian of the simple field kit in estimation of iodine content in the salt was in the content > 15 ppm -< 30 ppm, that were 87.5% for house wives and 86.7% for "kader". It's Predictive Positive Value (PPV) in that iodine concentration was 88% for the house wives and 87% for the caders. Its sensitivity was above 45% and its true prevalence (Se + Sp) was above 100% for all iodine concentration. Recomendatlons: Further test for this field kit was suggested to be performed particularly its stability during storage. Keyswords: Iodated salt, a simple field kit, semi-quantities.